Time is wasting: con/sequence and s/pace in the Saw series. Issue 2 (1st November 2010) - Jones, Steve
Horror film sequels have not received as much serious critical attention as they deserve this is especially true of the Saw franchise, which has suffered a general dismissal under the derogatory banner Torture Porn. In this article I use detailed textual analysis of the Saw series to expound how film sequels employ and complicate expected temporal and spatial relations in particular, I investigate how the Saw sequels tie space and time into their narrative, methodological and moral sensibilities. Far from being a gimmick or a means of ensuring loyalty to the franchise (one has to be familiar with the events of previous episodes to ascertain what is happening), it is my contention that the Saw cycle directly requests that we examine the nature of space and time, in terms of both cinematic technique and our lived, off-screen temporal/spatial orientations.